Differentiation of fetal liver cells in vitro. - Freeman, A E (1981)
Fetal mouse liver hepatocytes proliferate on a substrate of irradiated pigskin epidermis scored with scalpel blade slits to permit cell access to the basement membrane. At the time the cells are explanted, fetal genes, such as those responsible for production of alpha-fetoprotein (AFP) and gamma-glutamyltransferase (GGTase), are strongly expressed. The levels of GGTase decrease rapidly and become undetectable within 2 weeks. The levels of AFP decrease more gradually but become undetectable after 3-5 weeks in culture. As the AFP levels decrease, there is a concomitant increase in albumin production. Hydrocortisone prolongs production of AFP (for up to 8 weeks) but not of GGTase, and it decreases albumin production for up to 8 weeks. Once cells lose AFP expression, addition of hydrocortisone does not restart it. Based on these data, fetal mouse liver hepatocytes, cultured on pigskin, seem to be an excellent in vitro model for liver cell maturation.